Developing advanced literacy in first and second languages : meaning with power - Schleppegrell, Mary; Colombi, Cecilia (Lawrence Erlbaum Associates, 2002)
This book addresses the linguistic challenges faced by diverse populations of students at the secondary and post-secondary levels as they engage in academic tasks requiring advanced levels of reading and writing. It aims to contribute to research and pedagogy on advanced literacy development.